Ethnopharmacological Approaches for Dementia Therapy and Significance of Natural Products and Herbal Drugs - Tewari, Devesh; Stankiewicz, Adrian M.; Mocan, Andrei; Sah, Archana N.; Tzvetkov, Nikolay T.; Huminiecki, Lukasz; Horbańczuk, Jarosław O.; Atanasov, Atanas G. (Frontiers in Aging Neuroscience, 2018)
Dementia is a clinical syndrome wherein gradual decline of mental and cognitive capabilities of an afflicted person takes place. Dementia is associated with various risk factors and conditions such as insufficient cerebral blood supply, toxin exposure, mitochondrial dysfunction, oxidative damage, and often coexisting with some neurodegenerative disorders such as Alzheimer’s disease (AD), Huntington’s disease (HD), and Parkinson’s disease (PD). Although there are well-established (semi-)synthetic drugs currently used for the management of AD and AD-associated dementia, most of them have several adverse effects. Thus, traditional medicine provides various plant-derived lead molecules that may be useful for further medical research. Herein we review the worldwide use of ethnomedicinal plants in dementia treatment. We have explored a number of recognized databases by using keywords and phrases such as “dementia”, “Alzheimer’s”, “traditional medicine”, “ethnopharmacology”, “ethnobotany”, “herbs”, “medicinal plants” or other relevant terms, and summarized 91 medicinal plants that are traditionally used to treat dementia. Moreover, we highlight five medicinal plants or plant genera of prime importance and discuss the physiological effects, as well as the mechanism of action of their major bioactive compounds. Furthermore, the link between mitochondrial dysfunction and dementia is also discussed. We conclude that several drugs of plant origin may serve as promising therapeutics for the treatment of dementia, however, pivotal evidence for their therapeutic efficacy in advanced clinical studies is still lacking.